Living in a Parallel Universe: From Brussels to Orbán, and On - Troha, Tadej (Filozofski vestnik, 2019)
The European Union, as a political project epitomising the idea of the end of history, has put a great deal of effort into completing the processes of enlargement, integration, and democratisation, but has thus far failed to find a technical solution that would convincingly link the “by” and “of” the European people. In this paper we discuss several recent developments in European politics that provide evidence that this deficiency has reached a critical point. First, the failure of the Spitzenkandidaten model in the 2019 European elections; second, Viktor Orbán’s political interventions aimed at restoring the power of the nation-states within the EU; third, European Commission President Ursula von der Leyen’s decision to create a new post in her administration dedicated to “protecting our European way of life.” Drawing on the idea of “imitation” and “reverse imitation” developed by Ivan Krastev and Stephen Holmes, we argue that the European Union has recently entered its end phase, the stage of auto-imitation.